Alternative methodology for chitin–hydroxyapatite composites using ionic liquids and supercritical fluid technology. (September 2013) - Silva, Simone S; Duarte, Ana Rita C; Oliveira, Joaquim M; Mano, João F; Reis, Rui L
An alternative, green method was used to develop chitin-based biocomposite (ChHA) materials by an integrated strategy using ionic liquids, supercritical fluid drying, and salt leaching. ChHA matrices were produced by dissolving chitin in 1-butyl-methylimidazolium acetate along with salt and/or hydroxyapatite particles and then subsequent drying. The ChHA composite formed had a heterogeneous porous microstructure with 65%–85% porosity and pore sizes in the range of 100–300 µm. The hydroxyapatite was found to be well distributed within the composite structures and had a positive effect in the viability and proliferation of osteoblast-like cells, in vitro . Our findings indicate that these ChHA matrices have potential applications in bone tissue engineering.